Interest Rate And Foreign Direct Investment In Sub-Sahara African Countries: The Comparison Between Asymmetric And Symmetric Effects (Ardl And Nardl Approach) - Isiaka Najeem Ayodeji; Osifalujo, Babatunde Bunmi; Taiwo, Oluwaseun Kayode (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The differences in the estimation techniques considered by the researchers in the previous study have continued to generate considerable arguments to ascertain the relationship between interest rate and foreign direct investment. This current study investigated the relationship between interest rate and foreign direct investment in selected Sub-Sahara African countries between 1990 and 2019. The data on foreign direct investment, interest rate, and exchange rate were gathered from World Bank Development Indicators and asymmetric or Nonlinear ARDL was considered for the analysis. It was revealed that though interest rate and real exchange rate have a significant effect on foreign direct investment in the symmetric model in the long –run but there were found insignificant in the short –run. Also, the interest rate and exchange rate have negative relationship with foreign direct investment in the short-run but interest rate was found positive with foreign direct investment in the long-run and exchange rate was negative. . It was revealed that in the short-run a positive changes in interest rate will attract foreign direct investment but in the long-run it would change and reduces foreign direct investment. However, a decline of interest rate tends to attract foreign direct investment in the short-run but will not attract foreign investment in the long-run. The ECM revealed that the error in the short-run will be adjusted in the long-run by 94.5% and 88%. The study recommends that lending rate should be increased by monetary authorities within short-period to attract foreign investors but exchange rate must be appreciating.